Cultural codes of fear : genre, gender, (male) madness - Polgar, Nataša (Array, 2020)
This paper focuses on a specific type of archival material from the first psychiatric institution in Croatia, the Stenjevec Royal National Institute for the Insane in Zagreb, today the Vrapče University Psychiatric Hospital, dating from the period from its foundation in 1879 until 1900. More specifically, it focuses on patient narratives featuring fantastical beings, i.e., narrations about their life relying on the genre of belief legends. Based on this material, which is considered to be an important albeit atypical folkloristic corpus, the paper analyzes and interprets the status and functions of the genre of belief legends (more specifically, the memorate) in daily life narratives, personal stories and in coding affects (primarily fear). The role of belief legends is examined not only from the perspective of oral tradition and literature, but also in terms of their social and psychological position, and through the lens of psychiatric discourse of the time, which recognizes such narratives merely as symptoms of madness, translating and coding them as the language of abnormality and psychopathology.